2020
DOI: 10.3991/ijep.v10i1.11551
|View full text |Cite
|
Sign up to set email alerts
|

Design of English Vocabulary Mobile Apps Using Gamification: An Indonesian Case Study for Kindergarten

Abstract: English is essential for children because it is an international language that is al-ways used in various fields, both in the world of work, education, economics, and social. One method of learning for children is by playing while learning. Gamification in the field of education is an educational approach to motivate stu-dents to enjoy learning by applying the game design. The purpose of this study is to approach the learning of English, specifically for children in kindergarten schools so that children will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…It has been observed that the primary goal of using the gamification concept in the language education process is to increase the motivation, engagement, and integration of students with the learning materials, instructions, and exercises, which is considered for some learners as a nonenjoyable task, especially for children. This finding is in line with the results that have been proposed by (Cruaud, 2016;Fogarty, 2019;Tamtama et al, 2020). Students were enthusiastic and felt engaged and mentally stimulated due to the activities and the willingness to participate.…”
Section: Learners' Opinions Perceptions and Attitudessupporting
confidence: 91%
“…It has been observed that the primary goal of using the gamification concept in the language education process is to increase the motivation, engagement, and integration of students with the learning materials, instructions, and exercises, which is considered for some learners as a nonenjoyable task, especially for children. This finding is in line with the results that have been proposed by (Cruaud, 2016;Fogarty, 2019;Tamtama et al, 2020). Students were enthusiastic and felt engaged and mentally stimulated due to the activities and the willingness to participate.…”
Section: Learners' Opinions Perceptions and Attitudessupporting
confidence: 91%
“…Gamification is defined as a process in which gaming elements are introduced into a nongame operation to make the whole process interesting; such as lucky draw, point systems, rewards and competitions (Deterding et al, 2011;Hitchens and Tulloch, 2018). Previous studies had been done on the effect of using games in educational and e-banking context (Tamtama, 2020;Rodrigues, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are also other important resources within the latest innovations in educational technology, such as the implementation of augmented reality as a catalyst for student motivation (Garzón et al, 2020;Hanid et al, 2020;Pochtoviuk et al, 2020) and the use of educational apps for mobile devices that can expand the limits of the virtual classroom, the face-to-face classroom and the learning experience itself (Blilat & Ibriz, 2020;Tamtama, 2020). Along these lines, in recent years, many educational projects related to revitalising the virtual classroom based on new digital video platforms (Basith & Syafi'i, 2020) and even projects based on the effect of specific apps based on social interactions (Cassel, 2021;Gulati et al, 2020) have also appeared. Another aspect related to educational technology is TPACK and the focus on the integration of technological resources and the analysis of student perception (Soler-Costa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%